If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2c+3=2(6+3c)+6c
We move all terms to the left:
2c+3-(2(6+3c)+6c)=0
We add all the numbers together, and all the variables
2c-(2(3c+6)+6c)+3=0
We calculate terms in parentheses: -(2(3c+6)+6c), so:We get rid of parentheses
2(3c+6)+6c
We add all the numbers together, and all the variables
6c+2(3c+6)
We multiply parentheses
6c+6c+12
We add all the numbers together, and all the variables
12c+12
Back to the equation:
-(12c+12)
2c-12c-12+3=0
We add all the numbers together, and all the variables
-10c-9=0
We move all terms containing c to the left, all other terms to the right
-10c=9
c=9/-10
c=-9/10
| 1/2x+2=x | | n-6/6=n-2/9 | | 2/3x-21/3=17 | | 1.75x+10=3.5x | | 4x+6(4x-3)=-8 | | -c/10+26=46 | | 7(−2k+4)−6=7k−20 | | M-4n=-6 | | 2-5m=-(5m+6) | | 3=-5x+2 | | 2/3(3x+)9=-2(2x+6) | | -3=-3x-2 | | 2x=5.5x+10 | | 8x+22=36 | | 17.4(z+5)=32 | | 4/3b-185/168=7/4b-1/3(4/3b+24/7) | | 2x+5+3x-1=20 | | 4x+21x-1=5(5x+9) | | 3x+40=58 | | -3=-3x³-2 | | 3n-2+2(2n+1=n+5n+7= | | -1(-1+7x)-6(-7-x)=36 | | 3x-5(x-4)=-9=5x=8 | | 2/3x^2+6=18 | | 3m/4-12=2m-7 | | 3(n-1)=3n-9 | | 2=1x+6 | | 74-13x=355 | | 16+6y=84 | | 2(4R+7)=8r+14 | | 6-3g=5g-10g+12 | | 32x=28*8 |